PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP FINANCIAL DISTRESS DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Gloria Kristiana Sembiring; Eli Safrida (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2026)
This study examines the financial distress of healthcare sector companies listed on the Indonesia Stock Exchange website from 2020 to 2024. This study uses financial distress as the dependent variable and two independent variables, leverage, liquidity, and profitability as moderating variables. The purpose of this study is to determine the effect of leverage and liquidity on financial distress, using profitability as a moderating variable. This study uses Zmijewski's model to predict financial distress in companies. Leverage is measured using the debt-to-asset ratio (DAR), and liquidity is measured using the current ratio (CR). Profitability is measured using the return on assets (ROA) indicator. The data sources used are secondary data obtained from the Indonesia Stock Exchange and the official websites of healthcare sector companies listed on the IDX from 2020 to 2024. The population of this study was 33 healthcare sector companies, and purposive sampling was used to select 17 companies as research samples. Data processing techniques used were descriptive statistics, logistic regression analysis, multicollinearity testing, classification tables, moderated regression analysis (MRA), and hypothesis testing. The results of this study indicate that DAR and CR have no effect on financial distress. Furthermore, ROA is unable to moderate the effects of DAR and CR on financial distress.